Robotic Assisted Living Donor Nephrectomies: A Safe Alternative to Laparoscopic Technique for Kidney Transplant Donation. Issue 3 (March 2022) - Spaggiari, Mario; Garcia-Roca, Raquel; Tulla, Kiara A.; Okoye, Obi T.; Di Bella, Caterina; Oberholzer, José; Jeon, Hoonbae; Tzvetanov, Ivo G; Benedetti, Enrico
Abstract : Objective: To review outcomes after laparoscopic, robotic-assisted living donor nephrectomy (RLDN) in the first, and largest series reported to date. Summary of Background Data: Introduction of minimal invasive, laparoscopic donor nephrectomy has increased live kidney donation, paving the way for further innovation to expand the donor pool with RLDN. Methods: Retrospective chart review of 1084 consecutive RLDNs performed between 2000 and 2017. Patient demographics, surgical data, and complications were collected. Results: Six patients underwent conversion to open procedures between 2002 and 2005, whereas the remainder were successfully completed robotically. Median donor age was 35.7 (17.4) years, with a median BMI of 28.6 (7.7) kg/m 2 . Nephrectomies were preferentially performed on the left side (95.2%). Multiple renal arteries were present in 24.1%. Median operative time was 159 (54) minutes, warm ischemia time 180 (90) seconds, estimated blood loss 50 (32) mL, and length of stay 3 (1) days. The median follow-up was 15 (28) months. Complications were reported in 216 patients (19.9%), of which 176 patients (81.5%) were minor (Clavien-Dindo class I and II). Duration of surgery, warm ischemia time, operative blood loss, conversion, and complication rates were not associated with increase in body mass index. Conclusion: RLDN is a safe technique and offers a reasonable alternative to conventional laparoscopic surgery, in particular in donors with higher body mass index and multiple arteries. It offers transplant surgeons a platform to develop skills in robotic-assisted surgery needed in the more advanced setting of minimal invasive recipient operations. Abstract : Supplemental Digital Content is available in the text